Efisiensi Teknis Cabai Merah di Indonesia - Nurmalita, Ika; Fariyanti, Anna; Novianti, Tanti (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2025)
There is a disparity in red chili production between actual and potential which causes the available supply to be inadequate to cover the high demand. Production problems could not only be identified through production factors but also other factors that contribute to the issue. Technical efficiency is an analytical method that measuring production factors and out-of-production factors simultaneously. This study aims to measure the level of technical efficiency of red chili farming, to analyze the factors that influence red chili production, and to analyze the factors that influence the technical efficiency of red chili farming. This study employs secondary data from the 2013 Agricultural Census Results of the 2014 Horticultural Crop Farming Household Subsector Survey (ST2013 SHR), Central Bureau of Statistics (BPS). Stochastic Frontier Analysis (SFA) is a method of estimating the level of technical efficiency of red chili farming and the factors that affect it. The results revealed that the average level of technical efficiency of Indonesian red chili farms was 0.6525. This level implies that Indonesian red chili farms still have the opportunity to be improved. Seeds, N-element fertilizers, P-element fertilizers, manures, pesticides and labor are factors that can affect red chili production. Education, technologies, participation in farmer groups, planting seasons, land types, cropping systems and certified seeds are factors that can raise the technical efficiency of red chili farming while access to credit and subsidies can reduce the technical efficiency of red chili farming. Assistance in the use of subsidies and credit is a policy the government could take in enhancing the technical efficiency of Indonesian red chili farms besides the technology use and dry season planting.